Ambiguity on the use of ‘Kami’ personal pronoun among foreign students - Abdul Kadir, Fatin Rabiha; Hamzah, Zaitul Azma Zainon; Che Rodi, Rozita; Kamaruddin, Rohaidah (Human Resource Management Academic Research Society, 2022)
The aim of the study is to explore the ambiguity that occurs through the use of Malay Language Personal Pronouns (PP) among foreign students. Hence, this study was carried out to identify and analyze ambiguity in the use of the reference personal noun 'We' among foreign students. This study is a field study and the study data was obtained using observation methods and interviews. Next, this PP usage data is recorded using a conversation recording tool. The location of this study is at the International Modern Arabic School, Putrajaya, Malaysia. A total of 24 samples were selected as respondents using non-probability sampling techniques. The findings found that there are several factors that cause the ambiguity of PP and the English translation of "we" also affect the understanding of foreign speakers.